Factors that Influence Career Choice of Graduating Pharmacy Students - Gargalicano, Charles Angel G.; De Oca, Phillip Raymund; Galicia, Hernane Jr. S.; Arosa, April Aileen Mae; Radadon, Shania Tyne A.; Gargalicano, Florida G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The adoption of the “nine-star pharmacist” concept by the International Pharmaceutical Federation has transformed the pharmacy practice from a drug and quality control-focused profession to a multifaceted field. However, there is still inequitable pharmacist distribution among career sectors. Also, alarming is the exceeding interest in a specific pharmacy field. Hence, it is crucial to assess pharmacy students' attitudes and preferences toward various pharmaceutical sectors. This descriptive research determined the career preference of 4th- year Pharmacy students of a Private College for Academic year 2021- 2022. It also determined the factors that influence their choice. Data analysis was done using frequency, percentage, mean, Standard Deviation, and Kruskal-Wallis in SPSS. Results revealed that most graduating prefer community pharmacy as their career choice. It also highlighted that experience of the curriculum course, training, influence of family & friends, and knowledge of the career opportunities in various pharmacy fields are factors that influence their career choice. Lastly, career preference alone is not a sufficient indicator to measure influence on choice of pharmacy graduates, and other variables for demographic profiling should be included. Moreover, a support program in the pharmacy curriculum for systematic delivery of information and skills pertinent to effective development of competent professional pharmacists is encouraged.